Steric Poly(diarylfluorene‐co‐benzothiadiazole) for Efficient Amplified Spontaneous Emission and Polymer Light‐Emitting Diodes: Benefit from Preventing Interchain Aggregation and Polaron Formation. Issue 7 (17th January 2020) - Bai, Lubing; Sun, Chen; Han, Yamin; Wei, Chuanxin; An, Xiang; Sun, Lili; Sun, Ning; Yu, Mengna; Zhang, Kangning; Lin, Jinyi; Xu, Man; Xie, Linghai; et al.
Abstract: The effect of introducing side‐chain steric hindrance on the optoelectronic properties of the well‐studied green light emitting polymer (poly(9, 9‐di‐ n ‐octylfluorene‐ alt ‐benzothiadiazole), F8BT) is investigated by means of replacing the 9, 9‐dioctylfluorene unit by two novel steric hindrance functionalized monomers, namely, poly(9, 9‐diarylfluorene‐ alt ‐benzothiadiazole) (FDFBT) and poly(9, 9‐diarylfluorene‐4‐carbazole‐ alt ‐benzothiadiazole) (FCzBT). Bathochromic shifts of the optical spectra concomitant with enhanced photoluminescence quantum yields and improved film morphologies are found on the novel copolymers compared to F8BT. Femtosecond transient absorption spectroscopy demonstrates how steric hindrance effect in the novel copolymers manifests into enhanced stimulated emission and longer excited state lifetimes, associated with the suppression of polaron formation, all these being favorable features for light amplifying applications. Consequently, random lasing emission is achieved in films based on these copolymers with a threshold of three times lower than that of F8BT (22.95 µJ cm −2 for F8BT; 6.36 µJ cm −2 for FDFBT and 8.44 µJ cm −2 for FCzBT). Polymer light‐emitting diodes based on the novel copolymers exhibit performances comparable to the best reported on fluorene‐based devices. All of these results manifest the great potential of these novel copolymers for the application in the field of light‐emitting devices. Abstract : A novel light‐emitting conjugated polymers design principle of side‐chain steric hindrance is applied to the synthesis of poly(9, 9‐di‐ n ‐octylfluorene‐ alt ‐benzothiadiazole) (F8BT) derivatives, and its ability to enhance the photoluminescence quantum yield, optimize the film morphologies, and inhibit the exciton–exciton annihilation is demonstrated. Compared to the parent ones, these novel steric F8BT derivatives show extremely low threshold lasing behavior and comparable efficient light‐emitting device performances.